Implementasi Instruksi Presiden No. 12 Tahun 2016 tentang Gerakan Nasional Revolusi Mental pada Badan Kesatuan Bangsa dan Politik Provinsi Sumatera Utara - Yurika Dewi; Budi Hartono; Adam Adam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study is to analyze the implementation of Presidential Instruction No. 12 of 2016 on the National Movement of Mental Revolution at the North Sumatra Provincial Unity and Community Agency and the constraints faced. The research method used is qualitative with data analysis techniques using a qualitative approach. Data collection was obtained from observation, interviews, and documentation. The research results refer to Edward III's theory with indicators of communication, resources, disposition, and bureaucratic structure. The findings show that the implementation of Presidential Instruction No. 12 of 2016 on the National Movement of Mental Revolution in terms of communication and resources has not been running well. Communication is still lacking, especially with external parties. The employees of the North Sumatra Unity and Community Agency also lack work ethics. However, in terms of disposition and bureaucratic structure, the implementation of the Presidential Instruction has been running well. The constraints faced by the agency in implementing the National Movement of Mental Revolution are the lack of public awareness of the importance of the movement, difficulty in socializing in remote villages, and the delay in the provision of funds, which often hinders the implementation of the policy.